Economic and commuting connections in the northern GCR - Mosiane, Ngaka; Murray, Jennifer (Gauteng City-Region Obervatory, 2022)
This Map of the Month illustrates some of the ways through which the core areas of the Gauteng City-Region (GCR) are interconnected with their peripheries, including those that are outside the Gauteng Province, but are within commuting distance. The connections are drawn as straight lines from the start to end points, representing some of the regional flows of goods, services, and people (particularly workers). These flows signify disparate types of relationships between the city region peripheries and core areas, involving the transporting of mining supplies from Gauteng to Rustenburg mining operations. They also indicate relationships of interdependence, including daily commutes from northern Tshwane and former KwaNdebele to the City of Tshwane. It suggests that railway lines, highways, and roads are among the government's most important development interventions. Ordinary people themselves turn those facilities into resources to cope with, rework, or even overcome their marginality. The resultant large-scale practices and spaces of mobility overcome the divide between the core and periphery.
This Map of the Month illustrates some of the ways through which the core areas of the Gauteng City-Region (GCR) are interconnected with their peripheries, including those that are outside the Gauteng Province, but are within commuting distance. The connections are drawn as straight lines from the start to end points, representing some of the regional flows of goods, services, and people (particularly workers). These flows signify disparate types of relationships between the city region peripheries and core areas, involving the transporting of mining supplies from Gauteng to Rustenburg mining operations. They also indicate relationships of interdependence, including daily commutes from northern Tshwane and former KwaNdebele to the City of Tshwane. It suggests that railway lines, highways, and roads are among the government's most important development interventions. Ordinary people themselves turn those facilities into resources to cope with, rework, or even overcome their marginality. The resultant large-scale practices and spaces of mobility overcome the divide between the core and periphery.
Keywords: Gauteng, peripheries